Architectural Design of Referral Patient Data Security using Advanced Encryption Standard - Romli, Moh. Ali; Zakariyah, Muhammad (Sistemasi: Jurnal Sistem Informasi, 2025)
Electronic medical record can manage various kinds of patient data in digital form. Patient data security is a priority that must be met by healthcare provider for referral process. One of the medical data exchange standards that is widely used is Health Level Seven (HL7) standard. The absence of security in the HL7 standard makes patient data vulnerable to digital attacks, information security disturbances, and can even disrupt the patient's own psyche. This study aims to create an architectural design as well as a prototype of a patient data security system that uses HL7 standard, by utilizing the Advanced Encryption Standard (AES) as a cryptographic algorithm. Architectural design for data exchange, can change HL7 data from plain text and unauthenticated data transmission to data with secure and protected protocols. The research method starts from requirements analysis and finished with making system prototypes and model evolution. The system that has been developed is deployed into a SaaS model on cloud computing. The SaaS architecture for securing patient referral data has been adapted to the stakeholders involved (users), the medical data exchange standard used (HL7 standard), workflow and data exchange processes, and the data security technique itself (AES).